Sa rikaw - Limayo, Kathleen Lei Patag 1990- (2012)
"Sa Rikaw is a documentary that centers on the culture loss of the Iraya Mangyang community in Magnot, Barangay Balao, Abra de Ilog, Occidental Mindoro. The film shows the discontinued use of the Irayan language by the community and how it has affected their lives as an ethnic tribe. It documents the last Irayan song, Sa Rikaw, that the community knows. The framework used for the documentary is Cultural Hegemony. Antonio Gramsci explains that a multi-cultural society is dominated by a social class or dominant culture. Cultural Hegemony is evident in the Iraya community's current situation, the losing of the Iraya language, formal pubic school education, consumerism, effect of mass media and the losing of the only Iraya song left, Sa Rikaw."